Prioritization of ISO/IEC 25012 Data Quality Dimensions Using the AHP Technique - Iwata, Cláudio Keiji; Ito, Márcia (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2025)
This article presents a method for prioritizing data quality dimensions based on the ISO/IEC 25012 standard, using the Analytic Hierarchy Process (AHP) technique. The method assists in assessing data quality for training predictive models, considering the relevance of dimensions according to the application context. The research combines qualitative analysis, through the collection of expert judgments, and quantitative analysis to calculate relative weights between the selected dimensions. To assess the method’s reproducibility and applicability, a simulation was conducted for a predictive model in hospital bed management. The simulation results indicate the feasibility of guiding data quality improvement actions and strengthening information governance for use in predictive modeling.